Cyberbullying prevention and intervention programs - are they enough to reduce the number of online aggressions? - Zavoianu, Elena; Pânișoară, Ion-Ovidiu (Journal of Education Culture and Society, 2020)
Aim. In order to provide a complete image of this phenomenon in the world and how different countries are dealing with it, I analysed some reasearch regarding the methods of prevention and intervention in cyberbullying that they have adopted.Methods. After studying the programs implemented in other countries, I counducted a research on 22 psychologists from Romania in order to find out their oppionions about these programs.Conclusions. The results of this research study showed that the intervention and prevention programs adopted by different countries are esential in reduction of the cyberbullying cases, but these programs have to be combined with personalised intervention.